IMPORTANCE OF FARMER – INSTITUTIONS RELATIONSHIP INTENSITY FOR FARM DEVELOPMENT - Ostromęcki, Artur; Mantaj, Andrzej; Zając, Dariusz (Acta Scientiarum Polonorum. Oeconomia, 2011)
The aim of the paper is to assess importance of the relationship, at various levels of its intensity, between farmers and the institutional environment of agriculture for farm development. The data source derives from the results of questionnaire surveys conducted among farmers – owners of agricultural holdings in the south-east of Poland, i.e. the area of Świętokrzyskie, Małopolskie and Podkarpackie provinces. The research results demonstrated that the degree of intensity of farmers` interactions with institutions is directly linked to resources, organization of the production process and the production performance of the agricultural holdings. High intensity of farmer-institutions interactions facilitates the process of introduction of changes in agricultural holdings with the use of the European Union fi nancial support. However, the rule applies mainly to the larger-in-size and economically stronger holdings and may consequently lead to growing polarization of farms in the highly fragmented structure of agricultural holdings in the south-east of Poland.